Teori-Teori Komunikasi Massa dalam Perspektif Islam - Nazarullah Nazarullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The science of Islamic communication, as well as the science of general communication, discusses about human beings. Communication exists in all aspects of human life. Communication has basically been taught by the Creator, Allah SWT, through the holy book of the Qur'an about how important communication for mankind, especially Muslims. Efforts to convey the message of speech to influence people called the mass, must use theories of mass communication in accordance with the principles and teachings of Islam, which comes from the Koran and Hadith as well as ijmak ulama. Various theories have actually existed since the Qur'an even since this nature was created, but its development continues to evolve with the times